1987
DOI: 10.1007/bf00035906
|View full text |Cite
|
Sign up to set email alerts
|

Study of factors affecting the culture of Brassica napus L. and B. juncea Coss. mesophyll protoplasts

Abstract: Various factors affecting the culture of Brassica napus and B. juncea mesophyll protoplasts were examined in order to develop suitable culture media for these species. The basic components (salts and vitamins) of culture media K3 and Kao best supported cell division and colony development in protoplast culture of both species. The addition of casamino acids to Kao's medium resulted in colony browning in B. napus genotypes. B. napus protoplasts grew well with glucose as the osmotic stabilizer, whereas B. juncea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Kao & Seguin-Swartz (1987) also observed that the frequency of protoplast division was low and colony development was poor when mesophyll protoplasts of B. napus and B. juncea were cultured in this medium. All Brassica cultivars gave their lowest frequency of cell division when their protoplasts were cultured in a modified NN medium.…”
Section: Effects Of Culture Medium On Cell Wall Regeneration and Cellmentioning
confidence: 86%
“…Kao & Seguin-Swartz (1987) also observed that the frequency of protoplast division was low and colony development was poor when mesophyll protoplasts of B. napus and B. juncea were cultured in this medium. All Brassica cultivars gave their lowest frequency of cell division when their protoplasts were cultured in a modified NN medium.…”
Section: Effects Of Culture Medium On Cell Wall Regeneration and Cellmentioning
confidence: 86%
“…The protoplast bioassays were conducted with mesophyll protoplasts of a number of cruciferous species (B. carinata Braun, B. juncea, B. napus, and Sinapsis alba L.). The protoplasts were isolated from plants grown in vitro and cultured in vitro according to Kao and Séguin-Swartz (1987). Protoplast viability was assessed visually or with fluorescein diacetate (Heslop-Harrison & HeslopHarrison 1970).…”
Section: Phytotoxinsmentioning
confidence: 99%
“…Plant regeneration has been reported from protoplasts derived from many different types of tissues, including leaves (Kartha et al 1974;Thomas et al 1976;Li & Kohlenbach 1982;Pelletier et al 1983;Glimelius et al 1984;Kao & Seguin-Swartz 1987), roots (Xu et al 1982), stem embryos , hypocotyls (Glimelius 1984;Chuong et al 1985; Barsby et al 1986), and stem cortical strips (Klimaszewska & Keller 1987). Generally, these systems required high plating densities of protoplasts to initiate division, and plating efficiencies were low.…”
Section: Introductionmentioning
confidence: 99%